Technopedagogy Approach in Classroom Management Strategy in Fiqh Learning at Madrasah Aliyah - Aidzullah Aidzullah; Sitti Jamilah Amin; Muh. Akib; Muhammad Saleh; Ahdar Ahdar (Universitas Negeri Padang, 2025)
The advancement of digital technology in the Industrial 4.0 era has changed educational practices, including Islamic religious education, especially Fiqh learning. This study examines integrating digital technology in classroom management strategies in Fiqh learning at MAN 2 Parepare, Indonesia. Using a phenomenological qualitative approach, data were collected through observation, interviews, and documentation from teachers, students, and school leaders between February and April 2025. Findings show that tools such as Google Classroom, Quizizz, and interactive videos increase student engagement and create a dynamic learning environment. Adaptive classroom management strategies, including blended learning and positive reinforcement, support a structured and motivating atmosphere. However, challenges such as limited infrastructure, low digital literacy and digital distraction still exist, addressed through teacher training and access to flexible materials. This research confirms the potential of the technopedagogical approach to innovate Fiqh education, emphasizing the importance of a balanced integration of technology and pedagogy.